The role of apelin in cancer - Agarwala, Yuki; Sharma, Rohini (Frontiers in Oncology, 2025)
Apelin is widely expressed in the body. Apelin is secreted as a propeptide and is proteolytically cleaved into six main isoforms. As an adipokine, apelin has a cardio- and neuroprotective role and is involved in angiogenesis in healthy tissue. Recently, numerous roles of endothelial cell-derived apelin on cancer cells have been uncovered, including angiogenesis, cell proliferation, and cellular invasion. Studies have reported elevated apelin levels in tumor tissue of patients with cancer compared to healthy controls, highlighting its role in determining prognosis. Research suggests that inhibiting apelin reduces tumor invasiveness and angiogenesis and further mechanistic studies are required to realize the full potential of therapeutics targeting apelin in malignancy.